Antiseizure properties of fenamate NSAIDs determined in mature human stem-cell derived neuroglial circuits - Salmanzadeh, Hamed; Halliwell, Robert F. (Frontiers in Pharmacology, 2024)
Repeated and uncontrolled seizures in epilepsy result in brain cell loss and neural inflammation. Current anticonvulsants primarily target ion channels and receptors implicated in seizure activity. Identification of neurotherapeutics that can inhibit epileptiform activity and reduce inflammation in the brain may offer significant benefits in the long-term management of epilepsy. Fenamates are unique because they are both non-steroidal anti-inflammatory drugs (NSAIDs) and highly subunit selective modulators of GABAA receptors. In the current study we have investigated the hypothesis that fenamates have antiseizure properties using electrophysiologically mature human stem cell-derived neuro-glia cell cultures, maintained in long-term culture, and previously shown to be sensitive to first, second and third generation antiepileptics. Mefenamic acid, flufenamic acid, meclofenamic acid, niflumic acid, and tolfenamic acid (each tested at 10-100M) attenuated 4-aminopyridine (4-AP, 100M) evoked epileptiform activity in a dose-dependent fashion. These actions were as effective diazepam (3-30M) and up to 200 times more potent than phenobarbital (300-1000M). The low (micromolar) concentrations of fenamates that inhibited 4-AP evoked epileptiform activity correspond to those reported to potentiate GABAA receptor function. In contrast, the fenamates had no effect on neural spike amplitudes, indicating that their antiseizure actions did not result from inhibition of sodium-channels. The antiseizure actions of fenamates were also not replicated by either of the two non-fenamate NSAIDs, ibuprofen (10-100M) or indomethacin (10-100M), indicating that inhibition of cyclooxygenases is not the mechanism through which fenamates have anticonvulsant properties. This study therefore shows for the first time, using functionally mature human stem cell-derived neuroglial circuits, that fenamate NSAIDs have powerful antiseizure actions independent of, and in addition to their well-established anti-inflammatory properties, suggesting these drugs may provide a novel insight and new approach to the treatment of epilepsy in the future.